INCREASING THE PRODUCTIVITY OF NATURAL RUBBER PRODUCTION PROCESS WITH GREEN PRODUCTIVITY APPROACH: CASE STUDY IN PT X - M. Arif Darmawan, Bangkit Wiguna, Marimin, Machfud TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
ABSTRACT Productivity is an inseparable and important issue in every part of the industrial world. It has become one of several sustainability indicator of industry in the future. Process productivity can be improved by reducing the waste generated from it. The purpose of this study was to improve natural rubber production process in the PT X based on the Green Productivity concept. The current state analysis of green productivity measurement was used by using the green productivity indexing (GPI) method. The current state GPI measurement result for the production of ribbed smoked sheet was 0.27, while the GPI of brown crepe products result was 1.09. There were four alternative strategies to improve the green productivity in the PT X based on expert opinion,i.e. optimization of production process, raw material characteristics control, supporting material substitution, and reuse water. By using Analytical Hierarchy Process (AHP), the reuse of water process was the alternative strategy choosen, with 0.37 for the weight value. The implementation of the selected alternative strategy showed the reduction of the environmental impact of 3.57 for the production of ribbed smoked sheet and 0.54 for the production of brown crepe. The implementation of the selected alternative strategies also showed the green productivity increased to 0.690 for the production of ribbed smoked sheet with 2.57 GP ratio and 3.89 for brown crepe product with 3.57 GP ratio. Keywords: natural rubber, green productivity, Analytical Hierarchy Process, GP ratio